Effects of Echium plantagineum L. Bee Pollen on Basophil Degranulation: Relationship with Metabolic Profile - Moita, Eduarda (Molecules, 2014)
This study aimed to evaluate the anti-allergic potential of Echium plantagineum L. bee pollen and to characterize its primary metabolites. The activity of E. plantagineum hydromethanolic extract, devoid of alkaloids, was tested against β-hexosaminidase release in rat basophilic leukemic cells (RBL-2H3). Two different stimuli were used: calcium ionophore A23187 and IgE/antigen. Lipoxygenase inhibitory activity was evaluated in a cell-free system using soybean lipoxygenase. Additionally, the extract was analysed by HPLC-UV for organic acids and by GC-IT/MS for fatty acids. In RBL-2H3 cells stimulated either with calcium ionophore or IgE/antigen, the hydromethanolic extract significantly decreased β-hexosaminidase release until the concentration of 2.08 mg/mL, without compromising cellular viability. No effect was found on lipoxygenase. Concerning extract composition, eight organic acids and five fatty acids were determined for the first time. Malonic acid (80%) and α-linolenic acid (27%) were the main compounds in each class. Overall, this study shows promising results, substantiating for the first time the utility of intake of E. plantagineum bee pollen to prevent allergy and ameliorate allergy symptoms, although a potentiation of an allergic response can occur, depending on the dose used.